In Search of Identity in The Normal People (2018) by Sally Rooney - Fauziyyah, Hanna; Anwar, Desvalini (English Language and Literature, 2024)
This study about the search of identity by the two main characters in the novel Normal People (2018) by Sally Rooney. This study focuses on the internal and external factors that becomes challenges in the process of searching the main character's identity as well as the efforts used to overcome existing challenges. This analysis uses Erik H. Erikson's psychoanalysis theory which focuses on psychosocial. The method used in this research is descriptive qualitative with close reading techniques. The results of this research are that psychological condition is an internal factors that becomes a challenge in the process of searching the identity of the two main characters. Then, family, loved ones, and the society and cultural are external factors that become challenges in the process of searching of identity. Furthermore, the efforts are made by the main characters to overcome both the factors are by increasing self-awareness and quality, controlling ego, and trying to understand and appreciate life.